Pemerolehan Semantik Anak Usia Empat Tahun Delapan Bulan: Studi Deskriptif Arsyad Ghani - Pohan, Ratna Sari Dewi; Fitri, Laila; Irvan, Muhammad (Inovasi Pendidikan, 2024)
Semantics is a field of study concerned with meaning. When speaking, meaning becomes the main issue. The understanding of meaning is an activity that cannot be separated from other linguistic studies. Therefore, knowledge of the relationship between linguistic symbols or language units and their meanings is essential for effective communication. This study aims to describe the acquisition of semantics in the noun class, verb class, adjective class, and function words of a child named Arsyad Ghani, aged 4 years and 8 months. The data collection method used in this research is the conversational method with the elicitation technique. The informant sampling technique is total sampling, with a total of 200 words analyzed. The data were collected through audio recordings using input media. The data analysis process consisted of five stages: data reduction (summarizing and selecting key points), data display (presenting data in tables, pictograms, and similar forms), data verification (to summarize conclusions), data analysis, and drawing conclusions. Based on the research conducted on Arsyad, his semantic acquisition in the noun class consisted of 67 words out of 90, in the verb class 34 words out of 50, in the adjective class 35 words out of 46, and in the function word class 13 words out of 16. Thus, Arsyad’s overall semantic understanding across all Swadesh word classes is 74.50%. Keywords: semantic acquisition, child aged 4 years and 8 months, psycholinguistics